Educational Staff Perceptions of the Collection of Muhammadiyah Tarjih Decisions At Muhammadiyah University of Kendari - Awardin; Yusuf; Asman (IAIN KENDARI, 2026)
This study aims to examine educational staff’s perceptions of the Muhammadiyah Tarjih Decisions Compilation (HPTM), their understanding and practice of worship in accordance with the HPTM, as well as the reinforcement of Islamic values in line with the HPTM, and to identify the factors influencing the understanding and perceptions of educational staff at Muhammadiyah University (UM) Kendari. This study employs a mixed-methods approach with a sequential explanatory design. Quantitative data were collected via a Google Forms survey, while qualitative data were confirmed through in-depth interviews. Quantitative data analysis utilized descriptive statistics, whereas qualitative data were analyzed through data reduction, data presentation, and drawing conclusions. The research findings indicate that the majority of educational staff at UM Kendari hold positive, albeit diverse and varied, perceptions of HPTM. This is evident in their religious practices and work ethic, which align with Muhammadiyah’s religious teachings. These positive views are demonstrated by their familiarity with, knowledge of, understanding of, and practice of HPTM, as well as their strong work ethic and commitment to fulfilling their duties both on campus and within the community. However, there are still educational staff who are unaware of what HPTM is and have limited knowledge of its content. This is influenced by factors such as educational background, the intensity of religious guidance, and access to HPTM resources. This study implies that educational staff at UM Kendari should enhance their capacity and understanding of HPTM through formal Muhammadiyah training programs and regular religious study sessions. Thus, HPTM is not merely understood in a normative sense but is also practically implemented in daily life across various aspects of living